Etude bibliographique des activités biologiques et composés chimiques des trois plante médicinales :Ruta Chalepenses, Syzygium Aromaticum et Cupressus Sempervirens. - Djaffar, khadidja; Zenati, asma (My University, 2020)
The present bibliographic study has shown that Ruta Chalepensis (Rutacea) commonly called by the local population “Fidjel”, is a medicinal aromatic plant. Widely used in traditional medicine in many countries, as a laxative, anti-inflammatory, analgesic, antispasmodic, antiepileptic, emmenagogue and for the treatment of skin pathologies. Phytochemical results revealed the presence of coumarins , flavonoids, alkaloids, tannins, sterols and triterpenes. While the chemical screening Syzygium aromaticum known under the name of clove belonging to the Myrtaceae family revealed the presence of saponosides, tannins, anthocyanins, leuco anthocyanins, flavonoids, and Terpenes and Sterols in the plant studied. In addition, the essential oil of Syzygium aromaticum has strong antibacterial, antiviral and anti-inflammatory activity. The Cupressus Sempervirens is a very old tree which by its great medicinal wealth has crossed multiple cultures and civilizations. The branches of the Cypress mainly composed of flavonoids which will be used in the field of aromatherapy where the extracted essential oil has great utility in the capillaro-venous field. The fruiting cones of Cypress, composed mainly of condensed tannins, will find their importance in the field of phytotherapy or their venotonic and vasculoprotective actionThe proanthocyanidins of the cones of Cupressus Sempervirens have antiviral action. Studies have also proven the effectiveness of Provence Cypress cones on the Influenza and Coronavirus virus.